Oriente ocidente através: a melofanologopaica poesia de Paulo Leminski - Marcolino, Francisco Fábio Vieira (2007)
This work proposes a reading of Paulo Leminski´s poetry departing form the idea of capricho e relaxo and articulating semiotic consciousness and lirism., humour and meta-language. The analysis is made based on the melopoeia, phanopoeia, and logopoeia, categories developed by Ezra Pound, the entrangement (ostranenie) concept (Victor Chklovski) and the sound identity concept (Roman Jacobson). The context in which the poems are inserted is the new rising of the verse after the explicit dialogue between Leminski s poetry and the Concrete Poetry Movement in Brazil. In that sense, Leminski s diction, rooted on what we call condensation craftsmanship , it conciliates formal strictness and unruliness, the consciousness of the materiality of signs and colloquial language. Key words: meta-language, semiotic consciousness, colloquial language.